Net legitimacy: internet and social media exposure and attitudes toward the police. Issue 1 (2nd January 2020) - Intravia, Jonathan; Thompson, Andrew J.; Pickett, Justin T.
Abstract: Prior research suggests that exposure to adverse news stories involving the police negatively impacts consumers' attitudes toward these actors. Yet, most investigations have neglected to examine contemporary media diets, such as online consumption and engagement, and attitudes toward the police. Using a sample of mostly young adults, the current study contributes to the media effects literature by examining the relationships between online (Internet and social media) consumption and engagement and attitudes toward police legitimacy. Results indicate that consuming negative police stories on the Internet is associated with perceiving the police as less legitimate. Furthermore, this relationship varies by political ideology but not race. Findings and direction for future research are discussed.